Frosted branch angiitis in an AIDS patient with cytomegalovirus retinitis. (November 2016) - Mao, Feifei; Wu, Jianhua; Sun, Huiyu; You, Qisheng; Li, Dan
Summary: A case of frosted branch angiitis in an AIDS patient with cytomegalovirus (CMV) retinitis is reported. The use of PCR techniques for CMV DNA detection in intraocular fluid was helpful in this situation. The appropriate therapy was given promptly due to the timely diagnosis based on this assay.